1995
DOI: 10.3102/00028312032002285
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Gifted and Talented Programs on Academic Self-Concept: The Big Fish Strikes Again

Abstract: Participation in gifted and talented (G&T) programs is predicted to have negative effects on academic—but not nonacademic—self-concept on the basis of social comparison theory and Marsh’s big-fish-little-pond effect (BFLPE). In two studies, students in G&T programs experienced systematic declines in three components of academic self-concept (Reading, Math, School) over time and in relation to matched comparison students in regular mixed ability classrooms, but not in four components of nonacademic self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
149
1
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 252 publications
(161 citation statements)
references
References 36 publications
8
149
1
3
Order By: Relevance
“…In putting forth their argument Dai and Rinn stated that: "One can argue that gifted education provides an ideal test bed for the BFLPE theory" (p. 11) and that participating in a self-contained or short-term gifted program "gets close to the essence of the metaphor of a big fish in a little pond suddenly turned median or small when thrown into a big pond with many big or bigger fish" (p. 11). Whereas several of the studies of gifted education programs that they reviewed did show a decline in ASC consistent with BFLPE predictions (Marsh et al 1995;Zeidner and Schleyer 1998), others showed no decline or declines that returned to base-line levels when students in short-term gifted programs returned to regular classes. Based on these "mixed" findings, the authors concluded that findings from gifted education research were not entirely consistent with BFLPE predictions and that consequences of participation were more complex than suggested by BFLPE theory.…”
Section: Effects Of Ability Tracking Achievement Grouping and Giftementioning
confidence: 99%
See 3 more Smart Citations
“…In putting forth their argument Dai and Rinn stated that: "One can argue that gifted education provides an ideal test bed for the BFLPE theory" (p. 11) and that participating in a self-contained or short-term gifted program "gets close to the essence of the metaphor of a big fish in a little pond suddenly turned median or small when thrown into a big pond with many big or bigger fish" (p. 11). Whereas several of the studies of gifted education programs that they reviewed did show a decline in ASC consistent with BFLPE predictions (Marsh et al 1995;Zeidner and Schleyer 1998), others showed no decline or declines that returned to base-line levels when students in short-term gifted programs returned to regular classes. Based on these "mixed" findings, the authors concluded that findings from gifted education research were not entirely consistent with BFLPE predictions and that consequences of participation were more complex than suggested by BFLPE theory.…”
Section: Effects Of Ability Tracking Achievement Grouping and Giftementioning
confidence: 99%
“…For a large, nationally representative (US) database, Marsh and Rowe (1996) found that the BFLPE was clearly evident for students of all achievement levels and that the size of the BFLPE varied only slightly with individual student achievement. In two studies demonstrating BFLPEs in students attending gifted-and-talented programs, Marsh et al (1995) found no significant interaction between the size of the BFLPE and achievement level of individual students. In their cross-cultural study of the BFPLE in 26 countries, Marsh and Hau (2003) also found that the BFLPE did not vary with individual achievement levels.…”
Section: Moderation Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Marsh, Chessor, Craven, and Roche (1995) predicted varying development of different parts of the self-concept depending on educational experiences. In two studies of gifted pupils in grades four through six, experimental pupils attended a special class while control pupils attended regular mainstream, mixed ability classes.…”
Section: Types Of Curricular Interventions and Effects On Gifted Pupilsmentioning
confidence: 99%